PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Ega Apridinata; Dewi Zulvia (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Tax avoidance is one of the legal efforts made by companies in avoiding taxes, namely by taking advantage of the weaknesses contained in tax laws and regulations to reduce the burden of taxes paid, if tax avoidance activities are carried out in accordance with tax laws, then tax avoidance activities are legal And acceptable activities in the company. This study aims to find out and analyze how much the effect of Profitability (X1) Company Size (X2) on Tax Avoidance (Y) on Food and Beverage Companies on the Indonesia Stock Exchange. The method carried out in this study is quantitative using secondary data in the form of annual reports of Food and Beverage Companies for the 2018-2021 period. The analysis technique used is panel data regression. Based on the results of research (X1) produced with ROA has a significant effect on Tax Avoidance in Manan and Beverage Companies on the Indonesia Stock Exchange, and (X2) The Size of Companies Produced With SIZE does not affect Tax Avoidance in Food and Beverage Companies on the Indonesia Stock Exchange.